Analysis of Concept Understanding Test Items on Static Fluid Material Using Rasch Model - Irawan, Ivan Danar Aditya; Indraloka, Ristanti Mulia; Basri, Nur Akhyar; Salmah, Ummi; Parno, Parno (Jurnal Pendidikan Fisika, 2025)
Conceptual understanding is a vital component in physics education, particularly for static fluid concepts, which are often sources of misconceptions among students. Common misunderstandings include incorrect interpretations of hydrostatic pressure and Pascal's law. This study aims to develop and analyze a conceptual understanding test instrument for static fluid materials using the Rasch Model. A descriptive quantitative research design was employed, involving 75 eleventh-grade students from three high schools in Lumajang and Malang, selected through cluster random sampling. The instrument comprised 16 multiple-choice questions based on eight conceptual indicators and underwent expert validation by two physics teachers. Data were analyzed using the Winstep application to assess validity, reliability, difficulty level, and item discrimination. The results revealed that 12 out of 16 test items met the validity criteria, with an expert validation score of 98.3% categorized as "very valid." Item reliability was rated at 0.96 (very good), while person reliability was 0.47 (very poor), indicating significant variations in student responses. The difficulty levels were balanced: 2 very easy items, two easy items, five moderate items, one difficult item, and two very difficult items. Discrimination analysis grouped respondents into two categories and items into seven distinct groups, showcasing the instrument's effectiveness in identifying variations in student understanding. In conclusion, the developed instrument is valid and reliable for assessing students' conceptual understanding of static fluid topics. The study highlights the need for further validation with larger and more diverse samples to enhance the instrument's applicability across broader educational contexts.